Initiation of prostate cancer in mice by Tp53R270H: evidence for an alternative molecular progression - Ruth L. Vinall; Jane Q. Chen; Neil E. Hubbard; Shola S. Sulaimon; Michael M. Shen; Ralph W. DeVere White; Alexander D. Borowsky (The Company of Biologists, 2012)
SUMMARY Tp53 mutations are common in human prostate cancer (CaP), occurring with a frequency of ∼30% and ∼70% in localized and metastatic disease, respectively. In vitro studies have determined several common mutations of Tp53 that have specific gain-of-function properties in addition to loss of function, including the ability to promote castration-resistant (CR) growth of CaP cells in some contexts. To date, a lack of suitable mouse models has prohibited investigation of the role played by Tp53 mutations in mediating CaP progression in vivo. Here, we describe the effects of conditional expression of a mutant Tp53 (Tp53R270H; equivalent to the human hotspot mutant R273H) in the prostate epithelium of mice. Heterozygous "Tp53LSL-R270H/+" [129S4(Trp53tm3Tyj)] and "Nkx3.1-Cre" [129S(Nkx3-1tm3(cre)Mms)] mice with prostate-specific expression of the Tp53R270H mutation (p53R270H/+ Nkx3.1-Cre mice) were bred onto an FVB/N background via speed congenesis to produce strain FVB.129S4(Trp53tm3Tyj/wt); FVB.129S(Nkx3-1tm3(cre)Mms/wt) and littermate genotype negative control mice. These mutant mice had significantly increased incidences of prostatic intraepithelial neoplasia (PIN) lesions, and these appeared earlier, compared with the Nkx3.1 haploinsufficient (Nkx3.1-Cre het) littermate mice, which did not express the Tp53 mutation. PIN lesions in these mice showed consistent progression and some developed into invasive adenocarcinoma with a high grade, sarcomatoid or epithelial-mesenchymal transition (EMT) phenotype. PIN lesions were similar to those seen in PTEN conditional knockout mice, with evidence of AKT activation concomitant with neoplastic proliferation. However, the invasive tumor phenotype is rarely seen in previously described mouse models of prostatic neoplasia. These data indicate that the Tp53R270H mutation plays a role in CaP initiation. This finding has not previously been reported. Further characterization of this model, particularly in a setting of androgen deprivation, should allow further insight into the mechanisms by which the Tp53R270H mutation mediates CaP progression.